12-Lead Electrocardiograph Calibrator - Mahmud Ma'rufi; Imam Tri Harsoyo; Florentinus Budi Setiawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The research develops and evaluates a 12-lead Electrocardiograph (ECG) calibrator using ESP32 microcontroller technology to enhance calibration precision in clinical environments. Healthcare facilities need accurate ECG signal recording through portable calibration devices that maintain ≤ 5% error tolerance. Previous calibrator designs lack unified integration of complete 12-lead functionality, extensive BPM ranges, and variable amplitude control within single portable units. The methodology incorporates hardware-software development, voltage measurements across three assessment points (charger module, ESP32 output, Nextion LCD), BPM validation at four operational settings, and waveform analysis (normal, square) with amplitude evaluation across multiple sensitivities. Experimental results demonstrate an average total error of 1.2% for BPM and amplitude measurements, maintaining voltage stability within ± 5% tolerance limits. Performance analysis validates device reliability for ECG calibration applications, showing optimal performance with square waveform configurations. The ESP32-based calibrator proves technically viable and clinically safe, providing cost-effective, high-precision alternatives to existing solutions. Future development opportunities include triangular waveform integration, Wi-Fi connectivity for remote operation, and rapid calibration initiation features.